Risiko Pemanfaatan Air Baku POKMAIR Watumalang Melalui Tinjauan Cemaran Koliform - Pujiyati Pujiyati; Prabang Setyono; Wiryanto Wiryanto (Universitas Muhammadiyah Surakarta, 2019)
Watumalang, Wonosobo, is a district with substantial spring utilization (60.66%). Limited management in quality of water utilization is considered a risk to health, especially from coliform contamination. The purpose of this study is to assess the risk of using raw water of POKMAIR group (spring users), specifically from the coliform aspect. The study was conducted primarily by water sampling and respondent questionnaires. Data analysis was performed descriptively and correlatively. The result shows that 71% of water samples did not meet the requirements as clean water from the coliform aspect. Utilization risk assessment shows that 37.5% of high-risk villages. Further analysis shows that the closest relationship to coliform was the ownership of sanitation facilities (r -0,381).